Exploiting Synergies between Rooftop Solar PV and Energy Efficiency Investments in the Built Environment - Makumbe, Pedzi (World Bank, Washington, DC, 2018)
The synergies between rooftop solar PV (RPV) and energy efficiency (EE) investments in the built environment include lower specific transaction costs, optimized RPV systems, shorter project payback periods (compared to RPV-only projects), and, for EE, enhanced project visibility. These synergies improve the likelihood of project implementation, which in turn helps to reduce peak demand, increase environmental benefits, improve energy security, and lower energy bills. Because the methods of financing and implementing RPV and EE in the built environment are often similar, it is wise to consider including an EE component when investing in an RPV project, and vice versa.